2022
DOI: 10.1097/sla.0000000000005645
|View full text |Cite
|
Sign up to set email alerts
|

Surgeons’ Leadership Style and Team Behavior in the Hybrid Operating Room

Abstract: Objective: This study aimed to assess the relationship between surgeons’ leadership style and team behavior in the hybrid operating room through video coding. Secondly, possible fluctuations possible fluctuations in leadership styles and team behavior during operative phases were studied. Background: Leadership is recognized as a key component to successful team functioning in high-risk industries. The ‘full range of leadership’ theory is commonly used to evaluate leadership, marking transformational, transa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…To compare how roles adapted during instances of uncertainty associated with and without IAEs, the frequency of skills expressed was calculated 18 ; teamwork skills associated with an IAE were normalized by the sum of IAE durations whereas skills with “no IAE” were normalized by the sum of no-IAE durations. The frequency of teamwork skills per hour was analyzed in a 6 level (teamwork skill: 1: backup behavior vs 2: coordination vs 3: psychological safety vs 4: situation assessment and shared mental models vs 5: team decision-making and planning vs 6: team leadership) × 4 (role: 1: nurses vs 2: anesthetists vs 3: surgeons vs 4: trainees) × 2 (associated with IAE: no vs yes) mixed factors analysis of variance with repeated measures on the first 2 factors.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To compare how roles adapted during instances of uncertainty associated with and without IAEs, the frequency of skills expressed was calculated 18 ; teamwork skills associated with an IAE were normalized by the sum of IAE durations whereas skills with “no IAE” were normalized by the sum of no-IAE durations. The frequency of teamwork skills per hour was analyzed in a 6 level (teamwork skill: 1: backup behavior vs 2: coordination vs 3: psychological safety vs 4: situation assessment and shared mental models vs 5: team decision-making and planning vs 6: team leadership) × 4 (role: 1: nurses vs 2: anesthetists vs 3: surgeons vs 4: trainees) × 2 (associated with IAE: no vs yes) mixed factors analysis of variance with repeated measures on the first 2 factors.…”
Section: Methodsmentioning
confidence: 99%
“…This variation in leadership skill is consistent with recent research that a surgeon's overall leadership style (eg, transformative vs transactional vs passive) fluctuates within an operation in response to context (eg, surgical phase). 18 Although most successful leaders modify their style to meet circumstances, this adaptation may be less intuitive for some new surgeons who could benefit from explicit mentorship and formal training in adaptive leadership. 29…”
Section: Skills Consistently Expressedmentioning
confidence: 99%
See 2 more Smart Citations
“…In spite of growing literature on safety conscientiousness, there is still a void of empirical evidence of PPE conscientiousness and its potential relation with the perceived PPE program. Prior safety research in multiple technological environments has revealed a positive association between an increased perception of safety policy by the employees and their safety conscientiousness (De Boeck et al 2017; Doyen et al 2020a and b; Soenens et al 2023). Accordingly, in this study we investigate as a first hypothesis if a similar positive association holds in the area of radiation shielding.…”
Section: Introductionmentioning
confidence: 99%